645‐GHz InP heterojunction bipolar transistor harmonic oscillator. Issue 22 (1st October 2017) - Yun, J.; Kim, J.; Yoon, D.; Rieh, J.‐S.
Abstract : 645‐GHz signal generation with a harmonic oscillator based on a 250‐nm InP heterojunction bipolar transistor technology is demonstrated. The oscillator is based on the common‐base cross‐coupled topology, generating a second harmonic signal through the push–push operation. The fabricated oscillator exhibits oscillation frequencies ranging from 561.5 to 645.1 GHz with bias variation. The measured peak output power is –17.4 dBm with a dc power dissipation of 49.3 mW (dc‐to‐RF efficiency of 0.04%). Additionally, terahertz imaging was successfully demonstrated with the developed oscillator employed as a signal source.